Investigation of Banana Biomass for Low Cost Biofuel Production - Terry , Teh Kim Leong (IRC, 2016)
In today’s world, fossil fuel had been the main source of energy for almost every nation in the world. Unfortunately, this source of energy are only able to sustain for 100 years to come. Besides that, burning of fossil fuel causes global warming and to a certain extent, causes extinction to certain species. Renewable sources of energy have to be used to replace this source of energy. Biomass is a better choice compared to the available renewable sources of energy due to its cheap cost and abundance. Banana plants are selected as the feed for biomass fuel. Various investigations have to be done on the parts of banana plant to determine which parts of the banana plant contain the highest starch concentration. The selected part is then used to undergo fermentation process to produce bioethanol which is a type of biofuel. This biofuel is a low cost biofuel as banana plants are often thrown away because the banana plants are unable to bear a second batch of fruits.